EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA ANAK DI SD INPRES 12/79 BENTENG TELLUE - Mulfiyanti, Dewi; Andi Satriana; Fitrah Ramadani; Gustika Sandra; Andi Sumarni (Nusantara Hasana Journal, 2025)
Improving health is one of the national development efforts to achieve awareness, willingness and ability to live a healthy life for every resident in realizing the highest degree of public health. Clean and Healthy Living Behavior in the school environment is an effort to empower students, teachers and the school community so that they can and are willing to carry out clean and healthy living behaviors in creating a healthy school. This community service activity aims to provide education about PHBS to elementary school students in S. The method of implementing the activity is in the form of education consisting of counseling, video screening, discussion and question and answer. Participants in educational activities are students in grades 1, 2, and 3.  The material presented was washing hands with soap before and after eating, eating healthy snacks, using clean and healthy latrines, exercising regularly, eradicating mosquito larvae, not smoking in the school environment, disposing of garbage in its place, and doing community service work with school residents to create a healthy environment. This community service activity succeeded in increasing the knowledge and understanding of participants about PHBS where there was an increase in knowledge by 70%. PHBS education activities in schools can be continued in other schools as an effort to foster clean and healthy living behaviors at an early age.